Pembuatan Karbon Aktif dari Hasil Pirolisis Ban Bekas - Tutik Muji Setyoningrum; Agus Setiawan; Ganang Pamungkas (Eksergi, 2018)
Currently, alternative renewable energy is needed, one of which is RCO (Rubber Compound Oil) oil which is made from waste tires. The making of RCO oil causes problems in the form of carbon waste which, if discharged, will cause environmental impacts. Efforts are needed to deal with kabon waste resulting from used tire pyrolysis, one of which is the creation of activated carbon to increase the economic value of waste. So the purpose of this study is to study the operating conditions in the manufacture of activated carbon from waste produced by used tire pyrolysis. Activated carbon is one of the absorbents that can be used in material purification. This study makes activated carbon using a chemical activation method. KOH was chosen as activating agent and the activation temperature variable was used with temperature variations of 700, 800, and 900 °C with activation times for 30, 45, and 60 minutes. In this study, the best activated carbon was obtained with 900 °C operating conditions for 60 minutes which produced an active carbon surface area of 230 m 2 /g.